The Effect Of Perioperative I.V. Corticosteroids On Hearing Outcome Following Stapedotomy - Çelik, Çağrı; Emrah Ceylan, Mehmet; Aliyeva, Aynur; Düzenli, Ufuk; Dalgıç, Abdullah (ENT Updates, 2018)
Objective: The purpose of this study is to investigate the effect of steroids on postoperative hearing outcome in patients with a clinical diagnosis of otosclerosis, who received intraoperative steroid treatment during surgery for conductive-type hearing loss. Methods: Between January 2014 and January 2017, 106 patients, comprising 43 men (40.6%) and 63 women (59.4%) between the ages of 18-64 (mean age: 44.1 ± 11.5 years), who had been diagnosed with otosclerosis resulting in conductive-type hearing loss, were included in the study. The audiometric values obtained for patients who had received intraoperative intravenous steroids were analysed on a retrospective basis by comparing the pre- and post-operative situation. The group of all patients was then subdivided into two groups on the basis of whether or not they had received intraoperative steroids. These groups were then evaluated in terms of pre- and post-operative bone and air conduction levels and the differences investigated statistically. Results: Postoperative bone conduction averages for all the patients in both Group 1 and Group 2 were significantly improved at all frequencies, except at 4000 Hz, compared to the preoperative mean value. However, there was no statistically significant difference observed between patients who did receive intra-operative single-dose IV corticosteroid injections and patients who did not receive IV corticosteroid injections group in terms of preoperative and postoperative air-bone conduction levels. Conclusion: It is not necessary routinely to administer systemic corticosteroids in order to prevent perioperative sensorineural hearing loss during surgery for otosclerosis. However, perioperative corticosteroids may be helpful in preventing sensorineural hearing loss when there are conditions present that can lead to inner ear damage during the operation.